Non-Pharmacological Management of Sleep Disorders in the Older Adults: The Role of Aromatic Footbath-Hydrotherapy - Rizqi Wahyu Hidayati; Anastasia Suci Sukmawati; Yuli Astuti (Universitas STRADA Indonesia, 2026)
Background: The increase in physiological symptoms in the elderly has an impact on reducing the quality of sleep. This decrease in sleep quality has an impact on health both physically and psychologically. One of the psychological impacts is depression. Various studies explain that depression can lead to distortion of thoughts, decreased memory, increased risk of suicide, and death. Purpose: The aimed to determine the effectiveness of the complementary therapy, especially aromatic footbath-hydrotherapy in reducing sleep disorders among the elder adults. The potential harming of the study were allergic and foot-wound, however the researcher select the participants based on inclusions and exclusions criteria. Methods: The method used was quasi experiment with pre-post control group. The group was divided into three with the number of respondents, there was 39 elderly consumptions of Sahdu tea, 38 elderly consumptions of